2022
DOI: 10.1155/2022/2929695
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Prognostic Value and Immune Infiltration of IGFBP Family Members in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common primary malignant brain tumor in adults. The insulin-like growth factor-binding protein (IGFBP) family is involved in tumorigenesis and the development of multiple cancers. However, little is known about the prognostic value and regulatory mechanisms of IGFBPs in GBM. Oncomine, Gene Expression Profiling Interactive Analysis, PrognoScan, cBioPortal, LinkedOmics, TIMER, and TISIDB were used to analyze the differential expression, prognostic value, genetic alteration, biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Therefore, we inferred that the high-risk effect of RAB6C in UVM may be related to BAP1 mutation. IGFBP4 plays an oncogenic role in glioblastoma and renal cell carcinoma ( 31 - 33 ). The oncogenic role of IGFBP4 is induced by the Wnt/beta-catenin pathway in renal cell carcinoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we inferred that the high-risk effect of RAB6C in UVM may be related to BAP1 mutation. IGFBP4 plays an oncogenic role in glioblastoma and renal cell carcinoma ( 31 - 33 ). The oncogenic role of IGFBP4 is induced by the Wnt/beta-catenin pathway in renal cell carcinoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The six prognostic genes directly and indirectly participated in the immune response in numerous tumors, for instance, LGALS2 in triple-negative breast cancer ( 37 ), LAMP3 + dendritic cells in nasopharyngeal carcinomas ( 38 ), ICOS in the generation of Tregs in follicular lymphoma ( 35 ), FCAMR in lung squamous cell carcinoma ( 39 ), IGFBP4 in ewing’s sarcoma ( 40 ), C1QA in skin cutaneous melanoma ( 41 ). A previous study has suggested that IGFBP4 is associated with poor outcomes in glioblastoma ( 42 ). Interestingly, in diffuse large B cell lymphoma (DLBCL) patients, the C1qA [276] polymorphism of the A/A allele is an independent favorable prognostic factor for rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) as first-line therapy ( 43 ), while the expression level of LGALS2 was not associated with OS but was lower in tumors than in normal samples ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-dependent pathways for IGFBP-3:The binding of IGFBP-3 to IGF leads to the opening of the corresponding signaling pathway, which has been con rmed to be involved in the progression of glioma [19] ,Elevated serum IGF-1 is regarded as one of the recognized diagnostic markers of different tumors, especially brain malignant tumors.Ye Yun et al [20] detected the changes of IGF-1 and IGFBP-3 in normal brain tissue and glioma tissue by immunohistochemical staining,and were positively correlated with the pathological grade of glioma, suggesting that IGFBP-3 may be Enhanced the pro-tumor proliferative effect of IGF-1.…”
Section: The Pathway Of Action Of Igfbp-3 In Brain Tumormentioning
confidence: 99%
“…IGFBP-3 and Immune Cells:In the glioma microenvironment, immune cells activate corresponding signaling pathways to stimulate the expression of certain cytokines [25] .Scully et al [26] found that high expression of IGFBP-3 in tumor cell interstitium was positively correlated with tumor proliferation under high-fat environment;At the same time, increased CD8 was detected by immunohistochemistry, indicating that knockdown of IGFBP-3 caused CD8+T cell aggregation, which disappeared when knockdown of IGFBP-3 mice were fed a high-fat diet.This indicates that the presence of IGFBP-3 and high-fat environment will limit the anti-tumor proliferation effect of CD8+T and other immune cells.Wolf et al [27] found that the impaired immune function caused by severe burns leads to a weakened Th1 cell response and an increased Th2 cell response;Although there are still limited reports on IGFBP-3 and immune cells in brain tumors, this brings some enlightenment to study the relationship between IGFBP-3 and immune cells in brain tumors.…”
Section: The Relationship Between Igfbp-3 and The Brain Tumor Microen...mentioning
confidence: 99%